Правові проблеми децентралізації влади у контексті реалізації народного суверенітету в Україні - Богів, Я.; Bohiv, Ia. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проведено аналіз правових проблем процесу децентралізації влади, зокрема реалізації принципу субсидіарності як однієї із базових засад реформи місцевого самоврядування, в тому числі визначено теоретичний зміст вказаного принципу та особливості його реалізації у процесі внесення змін до Конституції України. Серед можливих напрямів правового забезпечення принципу субсидіарності місцевого самоврядування у сучасному конституційному процесі України виділено потребу більш чіткого визначення вказаного принципу, а також можливу фіксацію розподілу компетенції різних рівнів місцевого самоврядування безпосередньо у тексті Конституції України. The paper analyzes legal issues of decentralization of power, including the implementation of the principle of subsidiarity as one of the basic principles of local self-governing reform. The author has proved that the process of decentralization of power and development of civil society requires a clear definition of the status of the territorial community as the primary subject of local self-governing. Clear constitutional wording on issues of local importance should fully ensure the principle of subsidiarity of local selfgoverning. Therefore, issues of local importance as the basis of municipal power or the subject of the territorial community, require constitutional and legal fixation since «everything is allowed which is not explicitly prohibited by law». Thus, designing the activities of local government on the principle of subsidiarity requires from the state to give local communities the powers in the volume they can complete, to ensure their material basis and give them necessary and sufficient law-making functions.
Legal Issues of Decentralization of Power in the Context of National Sovereignty in Ukraine.
Keywords: народний суверенітет; децентралізація влади; принцип субсидіарності; місцеве самоврядування; people’s sovereignty; decentralization of power; the principle of subsidiarity; local selfgoverning